FRI0662 ACTIVATION AND LEUKOCYTE ADHESION IS ASSOCIATED WITH VASCULAR DAMAGE IN PATIENTS WITH RHEUMATOID ARTHRITIS AND PSORIATIC ARTHRITIS. (June 2019) - Aguilar-Zamora, Marta; Montolio-Chiva, L; Orenes Vera, Ana V; Vázquez-Gómez, I; Pérez, Isabel Andújar; García-Martínez, Patricia; Martínez-Ferrer, À; Valls-Pascual, Elia; Ybáñez-García, D; Sendra-García, A; Núñez-Monje, V; Torner-Hernández, I; et al.
Abstract : Background: Patients with inflammatory rheumatic diseases, such as rheumatoid arthritis (RA) or psoriatic arthritis (PsA), have a higher cardiovascular risk than the general population. There are data in other pathologies about the role of leukocyte adhesion on endothelial damage. Objectives: To evaluate the relationship between leukocyte adhesion and subclinical vascular damage in patients with RA and PsA. Methods: Observational, cross-sectional exploratory study. Patients with RA and PsA who had at least one previous vascular study were recruited in a tertiary hospital during a period of 3 months. All of them donated a sample of fresh blood. Neutrophils were isolated and perfused on a monolayer of healthy endothelial cells of the umbilical cord vein to evaluate its degree of activation, determining the leukocyte adhesion parameter. The expression of different adhesion molecules was analyzed by flow cytometry. We also gathered demographic (sex, age, BMI), clinical (disease duration, classical CV risk factors) and analytical (CRP, ESR) variables. The previous vascular study consisted of an exploration of the extracranial carotid tree with an Esaote MyLab70XVG ultrasound scanner with a linear probe (7-12mHz) and an automated program for measuring the carotid intima-media thickness (CIMT) using ("Quality intima media thickness in real-time, QIMT"), the presence of atheroma plaques as per the Mannheim consensus and the measurement of pulse wave velocity (VOP) using the Mobil or graph® device. We consider as pathological the vascular study with the presence of abnormal plaque and/or IMT (> 900μ) and/or VOP (≥ 10m/s). The statistical analysis was performed with the SPSS Statistics 22.0 program. Results: We included 27 patients, 18 women and 9 men, with a mean age of 58.07 (SD 11.64). Eight patients were diagnosed with RA and 19 with PsA, with mean disease duration of 14 years (SD 7.14). Of these 27 patients, 15 were on biologics, 11 were treated only with DMARDs and one patient was naïve for any immunomodulatory treatment. In addition, 14 (51.9%) were taking NSAIDs and 7 (25.9%) glucocorticoids. Regarding cardiovascular risk factors, 51.9% were exposed to tobacco, 25.9% suffered hypertension, 37% were dyslipidemic, 11% were diabetic and 11% were obese, with an average of 1.41 classic cardiovascular risk factors (SD 1.36) per patient. The previous vascular study had been considered pathological in 44.4% of the patients. A tendency to greater leukocyte adhesion was observed in those patients with pathological IMT values (p =0.059) and in those patients who presented atheromatous plaque (p = 0.66). No significant associations were found in relation to the rest of the adhesion parameters analyzed, nor could subanalysis be performed due to the small sample size. Conclusion: Our preliminary data suggest that an increase in leukocyte adhesion on the endothelium is involved in the mechanisms of subclinical atherosclerosis in patients with RA and PsA. Studies with a larger sample size will allow us to confirm these findings, as well as the factors implicated in their development. Disclosure of Interests: None declared